(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The article is devoted to a brief review of scientifi c-theoretical approaches in methodology of religion’s research in the XX century. Keywords: religion, the religious factor, the religious activities of state-confessional relations, international policy.